Role of S100 Proteins in Colorectal Carcinogenesis. (6th January 2016) - Moravkova, Paula; Kohoutova, Darina; Rejchrt, Stanislav; Cyrany, Jiri; Bures, Jan
Abstract : The family of S100 proteins represents 25 relatively small (9–13 kD) calcium binding proteins. These proteins possess a broad spectrum of important intracellular and extracellular functions. Colorectal cancer is the third most common cancer in men (after lung and prostate cancer) and the second most frequent cancer in women (after breast cancer) worldwide. S100 proteins are involved in the colorectal carcinogenesis through different mechanisms: they enable proliferation, invasion, and migration of the tumour cells; furthermore, S100 proteins increase angiogenesis and activate NF- κβ signaling pathway, which plays a key role in the molecular pathogenesis especially of colitis-associated carcinoma. The expression of S100 proteins in the cancerous tissue and serum levels of S100 proteins might be used as a precise diagnostic and prognostic marker in patients with suspected or already diagnosed colorectal neoplasia. Possibly, in the future, S100 proteins will be a therapeutic target for tailored anticancer therapy.